2016
DOI: 10.1016/j.cose.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Understanding online safety behaviors: A protection motivation theory perspective

Abstract: Internet users experience a variety of online security threats that require them to enact safety precautions. Protection Motivation Theory (PMT) provides a theoretical framework for understanding Internet users' security protection that has informed past research. Ongoing research on online safety recommends new motivational factors that are integrated here in a PMT framework for the first time. Using PMT, a cross-sectional survey (N = 988) of Amazon Mechanical Turk (MTurk) users was conducted to examine how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(152 citation statements)
references
References 43 publications
16
134
1
1
Order By: Relevance
“…Both LaRose et al (2008), who investigated the influence of prior exposure on intentions to adopt virus protection, and Tsai et al (2016), who investigated its impact on general security intentions, also found similar results. PMT (Rogers, 1975(Rogers, , 1983 proposes that perceived vulnerability has a direct impact on protection motivation; however, our results show no direct relationship between perceived vulnerability and intentions to comply with password guidelines.…”
Section: Discussionmentioning
confidence: 65%
“…Both LaRose et al (2008), who investigated the influence of prior exposure on intentions to adopt virus protection, and Tsai et al (2016), who investigated its impact on general security intentions, also found similar results. PMT (Rogers, 1975(Rogers, , 1983 proposes that perceived vulnerability has a direct impact on protection motivation; however, our results show no direct relationship between perceived vulnerability and intentions to comply with password guidelines.…”
Section: Discussionmentioning
confidence: 65%
“…Perceptions of time, financial cost, and cognitive effort of adopting a safe computing behavior are all important predictors of users’ decisions to protect themselves [14, 15, 18]. Therefore, we hypothesize that:…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…Each of these constructs can be placed in two intermediary cognitive processes which are the coping appraisal and threat appraisal processes [Figure 1]. [14]…”
Section: Introductionmentioning
confidence: 99%